METAMORPHOSED SULFIDE ORES FROM THE LUCHISTOE CU OCCURRENCE, SOUTH URALS - N.P. Safina; L.Ya. Kabanova; D.A. Kuznetsov; I.A. Blinov (Минералогия)
Sulfide ores from the Luchistoe copper occurrence, which are metamorphosed under thermal influence of the Mazar granitic intrusion, are similar in mineralogy and petrography with metamorphosed ores from the VHMS and copper scarn deposits of the Urals. The massive, disseminated, and banded ores with dominant pyrite and chalcopyrite are distinguished according to the textural features. The presence of the high-Fe sphalerite (up to 12 wt. % Fe), galena, molybdenite, pyrrhotite, rutile-ilmenite aggregates, and magnetite is typical of massive ores. The disseminated and banded ores are characterized by aggregates of ilmenite and rutile, ilmenite and Ti-magnetite, apatite, monazite-(Ce), and xenotime-(Y). The absence or insignificant amount of pyrrhotite, the presence of pyrite with graphical microstructures, and high-temperature exsolution structures of ilmenite+magnetite (T = 600–700 °C) are typical features of the ores studied. The disseminated and banded ores host hornblende, biotite, antophyllite, and cordierite, which reflect the processes of hornfels formation.